Financing of internationalisation process and its effects on Finnish SME - Saralidze, Mariam (2020)
This research focused on a study of how small businesses can launch their foreign operations, with a focus on the internationalisation process by Akukon OY. The study examined the factors and theories of internationalisation and it was found that the main forms of financing used by SMEs were self-funding, debts, equity, venture capital and grants by government and other associations. The study further examined how the various theories of internationalisation (Uppsala model, Dunning Eclectic Paradigm, and the Born Global theories) influenced the internationalisation of small and medium enterprises. Previous studies indicate that the Uppsala model influenced SMEs to internationalise slowly by first exporting to other markets. This means that the companies start by self-financing before graduating to other forms of financing such as debts and equity. In contrast, Dunning Eclectic Paradigm holds that internationalisation process should commence in instances where the company is likely to benefit or possess ownership, location and internalisation capabilities. Taking a different approach, Born Global theory looks at firms that start out as global organisations. The theory argues that such firms have advantages such as globally skilled founders that gives them an edge over domestic firms which expand later. By taking a qualitative approach, the study used extant theoretical approaches to develop interview questions, which were used to collect responses from face to face interviews. Four interviewees from the case company were sampled and targeted, and the data was analysed using content analysis. Three findings are notable. First, Akukon company gradually internationalised some of its operations and used minimal market commitment in its international operations. This proved that it was applying some aspects of Uppsala theory. It also invested in countries where the SME would have ownership advantages and market advantages by acquiring the best talent. This demonstrated that Akukon applied the eclectic paradigm. Akukon also had founders with international experience and possessed intangible assets. This proved that Akukon used Born Global strategy to some degree. The study demonstrates that SMEs that combine various approaches leverage their strengths and minimise their weaknesses.